"You have to regulate capitalism, otherwise the criminals will dominate it". Interview with Peter Flaschel - Peter Flaschel; Eckhard Hein; Torsten Niechoj (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
Peter Flaschel is Professor Emeritus at Bielefeld University, Germany. He holds a PhD degree in Mathematics and a Habilitation degree in Economics. He has extensively published on classical economics and heterodox macrodynamical model building. He was on numerous occasions Visiting Professor at the University of Technology, Sydney, and was invited in 2006 as Theodor Heuss Professor to the New School for Social Research, New York. He received an Opus Magnum Grant from the Fritz Thyssen/Volkswagen Foundations in 2007–2008.
Keywords: E0; 330; Interview; Capitalism